Expressão Diferencial de Genes Relacionados à Tolerância ao Estresse Salino (NaCl) em Arroz Vermelho (Oryza sativa L.) - Costa, Carolina Pereira (2014)
Rice (Oryza sativa L.) is one of the main agricultural products commercialized worldwide and the staple food for over half the world's population. In the Northeast of Brazil cultivated red rice has great socio-economic importance, besides being an integral and functional food associated with the production of antioxidant compounds. This grain presents high genetic variability and genes for resistance to biotic and abiotic factors. However, rice cultivation is susceptible to salts excess in the soil. In this context, in the present work, we intended to study: (a) the parameters of plant growth - SES classification system, biomass production of shoots and roots, shoot and root length and leaf area in twelve varieties of rice red with respect to tolerance to salt stress (NaCl) and select two varieties, one tolerant and one susceptible; (b) the relative expression of genes associated with salt stress OsHKT1;5, OsCIPK24, OsSOS1 and OsNHX1 in varieties of red rice selected as tolerant and susceptible to salt stress . Plant growth studies were performed in hydroponic cultivation system (IRRI ), where the treatment of 100 mM of NaCl showed the highest relative reduction in plant growth parameters when compared to 50 mM of NaCl . The fresh weight and the dry mass of shoots, the shoot length and the ratio of root dry mass to shoot dry mass showed high and significant correlations to the rating system SES. These parameters allowed the classification and selection of varieties 0801 and 0903 as tolerant and susceptible, respectively, during the initial phase of plant development. The relative expression studies were analyzed by comparing relative expression of Cq (2-ΔΔCq) determined after the reaction of qPCR. Differential behavior of the four genes analyzed among red rice tolerant (0801) and susceptible (0903) varieties in the saline treatment was observed. These differences in expression, respectively between tolerant and susceptible varieties, in the young leaves were derived from the OsCIPK24 (1.28 and 1.89 fold change) and OsHKT1;5 genes (1.53 and 1.70 fold change), while in the old leaves these differences were determined to OsSOS1 (-1.69 and 1.40 fold change) and OsCIPK24 (2.02 and 3.16 fold change) genes. The OsNHX1 gene showed no differential expression between tolerant and susceptible varieties, though having increased relative expression in old leaves (average of 9.18 fold change) compared to young leaves (average of 2.02 fold change). The classification of tolerant (0801) and susceptible (0903) varieties allowed the identification of differences in the expression of genes related to salt stress, contributing to elucidate the mechanisms that lead to the difference in the level of salinity tolerance of these varieties of red rice.